Microstructural analysis and multi‐response optimization of mechanical properties of bulk molding compound. Issue 1 (11th November 2021) - Rajaee, Pouya; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad; Amini, Nasrin
Abstract: In this article, the mechanical properties of commercial bulk molding compounds (BMC) based on the unsaturated polyester resin were maximized by optimizing glass fiber weight (FW) and fiber length (FL). An empirical design was utilized to study the influence of each parameter and its interaction on responses. Accordingly, three levels of FW (10, 15, and 20 wt.%) and FL (3, 6, and 12 mm) were used. A full factorial design was utilized to investigate the effect of each variable and their interaction on all responses. The addition of FW improved all the results except flexibility. In addition, all responses increased except the modulus of composites by increasing FL. The compound with 15 wt.% FW and 12 mm FL was chosen as the best toughness‐stiffness‐strength equilibrium among the specimens based on optimization outcomes. In addition, the R 2 obtained from the analysis of variance (ANOVA) and normal probability plots showed good compliance between the empirical results and those anticipated using a full factorial model. Abstract :